Key Factors in Helpfulness and Use of the SAFE Intervention for Women Experiencing Intimate Partner Violence and Abuse: Qualitative Outcomes From a Randomized Controlled Trial and Process Evaluation - Nicole E van Gelder; Suzanne A Ligthart; Karin A W L van Rosmalen-Nooijens; Judith B Prins; Sabine Oertelt-Prigione (JMIR Publications, 2023)
BackgroundMany women experience at least one type of intimate partner violence and abuse (IPVA), and although various support options are available, we still know relatively little about web-based interventions for IPVA survivors. We conducted a qualitative evaluation of the SAFE eHealth intervention for women experiencing IPVA in the Netherlands, complementing the quantitative evaluation of self-efficacy, depression, anxiety, and multiple feasibility aspects. ObjectiveThis study assessed users' experiences and what, according to them, were useful and helpful aspects of the intervention. MethodsThe intervention consisted of modules with information on relationships and IPVA, help options, physical and mental health, and social support. It also contained interactive elements such as exercises, stories from survivors, a chat, and a forum. A randomized controlled trial was conducted with an intervention arm receiving the complete version of the intervention and a control arm receiving only a static version with the modules on relationships and IPVA and help options. We gathered data through open questions from surveys (for both study arms; n=65) and semistructured interviews (for the intervention study arm; n=10), all conducted on the web, during the randomized controlled trial and process evaluation. Interview data were coded following the principles of open thematic coding, and all qualitative data were analyzed using qualitative content analysis. ResultsOverall, most users positively rated the intervention regarding safety, content, and suiting their needs, especially participants from the intervention study arm. The intervention was helpful in the domains of acknowledgment, awareness, and support. However, participants also identified points for improvement: the availability of a simplified version for acute situations; more attention for survivors in the aftermath of ending an abusive relationship; and more information on certain topics, such as technological IPVA, support for children, and legal affairs. Furthermore, although participants expressed a prominent need for interactive contact options such as a chat or forum, the intervention study arm (the only group that had these features at their disposal) mainly used them in a passive way-reading instead of actively joining the conversation. The participants provided various reasons for this passive use. ConclusionsThe positive outcomes of this study are similar to those of other web-based interventions for IPVA survivors, and specific points for improvement were identified. The availability of interactive elements seems to be of added value even when they are used passively. This study provides in-depth insight into the experiences of female IPVA survivors with the SAFE eHealth intervention and makes suggestions for improvements to SAFE and comparable web-based interventions for IPVA as well as inspiring future research. Furthermore, this study shows the importance of a varied assessment of an intervention's effectiveness to understand the real-world impact on its users. Trial RegistrationNetherlands Trial Register NTR7313; https://tinyurl.com/3t7vwswz